Thermal Analysis of Tilapia Fish Drying by Hybrid Solar Thermal Drying System - Al-Kayiem, H. (Penerbit Akademia Baru, 2022)
The present work presents a hybrid solar thermal drying of Tilapia fish to improve the product quality and satisfy the importers. The developed hybrid dryer utilized direct solar drying, a solar air heater and a thermal backup unit which sustains the drying process during the night, cloudy and rainy weather conditions. Besides, a new feature of the developed dryer utilizes the flue gas exhausted from the thermal unit to enhance the updraft in the drying chamber by re-injection of the flue gases in the chimney. The initial moisture content of the Tilapia fish used in the investigation was 246.6 on a dry basis, equivalent to 74 on a wet basis. The investigations were repeated three times on different days. Experimental results showed that the moisture content was reduced to an average final of 17.0 db (5.0 wb) within 17.5 hours, while in the open sun drying, it required around 48-72 hours. Hybrid solar drying required around 72 shorter time than open sun drying. The average overall drying efficiency of the developed system for drying Tilapia fish was 13.0. The Re-injection technique used in the present hybrid solarthermal system has excluded the need for an electric source for air extraction from the drying chamber, which is highly desired in the rural and fishery regions. Â© 2022. All Rights Reserved.